Concentrated lactic acid production from invert sugar in alkaline solution - Sirisangsawang, Rinlada; Kitchaiya, Prakob (My University, 2019)
High concentration of lactic acid production is not practical in industry, which is currently produced by fermentation. This work investigated lactic acid synthesis derived from invert sugar in an alkaline solution at low temperature under atmospheric pressure. 30 % invert sugar was continuously added into 3.5 - 8.5 M concentrated sodium hydroxide solutions in a semi-batch reactor at 30 – 80 °C. The central composited design (CCD) was used for design experiments and three variables such as reaction temperature, initial concentration of sodium hydroxide (NaOH) and feed time being investigated. The reaction temperature and initial concentration of NaOH were more pronounced on the yield. At 70 °C, 8.5 M NaOH, and feed time of 6 h. 76 % lactic acid yield was achieved. An independent study at 70 % invert sugar and 15 M NaOH solution caused runaway in a batch reactor, while the yield in a semi-batch reactor was 62 %.